RANCANG BANGUN E-LEARNING 2.0 BERBASIS WEBSITE PADA BALAI PENGEMBANGAN TENAGA KERJA (BPTK) DJOGJA BHAKTI UTAMA - Marhayu Marhayu; Viktor Handrianus Pranatawijaya; Tri Amri Wijaya (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Along with the development of information technology is growing rapidly, the need for a conceptand mechanism of IT-based teaching and learning becomes inevitable. As an agency ManpowerDevelopment Center "Bhakti Djogja Utama" which is a Course and Training Institute health managementengaged in non-formal education. In developing an E-Learning application uses the PHP programminglanguage applied to the system, HTML, CSS and J-query while for data storage using a MySQL databaseand application development methods waterfall. Manufacturing Website E-learning is becoming a mediaelectronic learning (e-learning). The website is also able to promote Workforce Development Center"Jogja Bhakti Utama" in the wider community through the virtual world.